Tocopherols in the Prevention and Treatment of Atherosclerosis and Related Cardiovascular Disease - Mathur, Pankaj (Clin Cardiol, 2015)
Oxidants/antioxidants play an important role in cellular homeostasis. The human body has endogenous molecules that work as antioxidants, such as glutathione, superoxide dismutase, peroxidases, and catalase. Exogenous substances in the diet, such as β‐carotene, ascorbate, and vitamin E, are vital antioxidants. Of these, vitamin E is likely the most important antioxidant in the human diet, and many studies have been performed to elucidate its role in health and disease. Vitamin E is a family of several compounds, of which α‐tocopherol is the most widely known analog. α‐Tocopherol exhibits antioxidative property in vitro and inhibits oxidation of low‐density lipoprotein cholesterol. In addition, α‐tocopherol shows anti‐inflammatory activity and modulates expression of proteins involved in the uptake, transport, and degradation of atherogenic lipids. Though α‐tocopherol exhibits important antioxidant, anti‐inflammatory, and antiatherogenic features in vitro, α‐tocopherol supplements have failed to consistently reduce atherosclerosis‐related events in human trials. The conflicting results have led to reconsideration of the importance previously given to α‐tocopherol and led to interest in other members of vitamin E family, especially γ‐tocopherol, which exerts a much more potent antioxidant, anti‐inflammatory, and cardioprotective effect than α‐tocopherol. This reconsideration has been backed by solid laboratory and clinical research. We suggest that the absence of γ‐tocopherol in traditional preparations may be one reason for the lack of consistent salutary effects of vitamin E preparations in clinical trials. This review summarizes our current understanding of tocopherols as antioxidant molecules and emerging evidence of an important role of γ‐tocopherol in the pathophysiology of atherosclerosis‐related cardiovascular disease.